PEMBERDAYAAN UMKM BERBASIS DIGITAL: SOSIALISASI DIGITALISASI KEPADA UMKM SNACK RUMAHAN - Puspa, Rani; Nopianti, Rina; Permana, Angrian; Khodijah, Ina; Yuliah, Yuliah; Afriani, Raden Irna (Yayasan Education and Social Center, 2025)
Digital transformation is an urgent need for MSMEs to increase the competitiveness of local products in the digital era. The UNIBA Community Service Team implemented a community service program in the form of Digitalization Socialization for Home-Based Snack MSMEs in Serang City, in September 2025. This activity aims to equip MSMEs with basic digital marketing skills, ranging from an introduction to digital platforms, promotional strategies, to the practice of creating simple online storefronts. The results of the activity showed an increase in participants' understanding and motivation to utilize social media as a means of marketing local products, such as cassava chips, onion sticks, and other household-based snacks. This program is the first step in encouraging the digitalization of micro-level MSMEs so they can adapt and thrive amidst the challenges of the digital economy era